Dramatic Texts and Records of Britain : A Chronological Topography to 1558 - Lancashire, Ian (Book collections on Project MUSE., 1984)
In 1800 entries this valuable reference work covers texts and records of dramatic activity for about 400 sites in Britain from Roman times to 1558.